Timeline of Intestinal Adaptation After Malabsortive Surgery: Effect of Luminal Nutrients, Biliopancreatic Secretion, and Glutamine Supplementation - Martínez-Moreno, José Manuel; Reyes-Ortiz, Alexander; Lage Sanchez, Jose María; Sánchez-Gallegos, María Pilar; García-Caballero, Manuel (Springer, 2017)
Three types of surgery were performed using a porcine model: biliopancreatic bypass (BPBP), massive (75%) short bowel resection as the positive control, and a sham operation (transection) as the negative control. We measured the height and width of intestinal villi, histidine decarboxylase (HDC) activity, and amount of HDC messenger RNA (mRNA) (standard diet or a diet supplemented with glutamine). An increase in HDC activity and mRNA expression was observed in the BPBP group. This increase coincided with an increase in the height and width of the intestinal villi. The increase in villus height was observed immediately after surgery and peaked at 2 weeks. Levels remained higher than those observed in sham-operated pigs for a further 4 weeks. The intestinal adaptation process in animals that underwent BPBP was less intense than in those that underwent massive short bowel resection and more intense than in those that underwent transection only. Supplementation with glutamine did not improve any of the parameters studied, although it did appear to accelerate the adaptive process.
Cronologia de la adaptación intestinal tras cirugía de Malabsortiva: Efecto de los nutrientes luminales, la secretación de Biliopancreático y la suplementación con glutamina
Keywords: Obesidad - Cirugía; Biliopancreatic bypass; Glutamine; Histidine decarboxylase; Intestinal adaptation; Malabsorptive surger